Exaptation in management: beyond technological innovations. Issue 1 (14th January 2019) - De Sordi, José Osvaldo; Nelson, Reed Elliot; Meireles, Manuel; Hashimoto, Marcos; Rigato, Carlos
Abstract : Purpose: Although exaptation is recognized as a means of creation capable of generating significant economic implications for organizations, this mechanism has not been explored in depth in the field of management, where it remains restricted to innovation and product research and development. With this limitation in mind, this study aims to explore and discuss exaptation along with other entities that are more greatly concerned with the interests of and direct contact with practitioners and academics in the field of management, such as processes, data, tacit knowledge and skills. Design/methodology/approach: For the purposes of this study, a comprehensive review of the literature on exaptation was conducted, and 46 entrepreneurs from companies of different sizes and segments were interviewed. Findings: The results of the review of the literature and interviews with entrepreneurs helped to identify and describe 13 cases of exaptation associated with nine different kinds of organizational entities. For four of these entities, which are closely associated with management, the restrictions of the business environment regarding the exaptation of these entities are discussed, together with the more favorable organizational structures for their occurrence. Practical implications: This paper discusses the exaptation to the four types of entity closely linked with management: tacit knowledge, data, process and skill. For each one of these entities the following is discussed: the organizational characteristics that hinder the exaptation of the entity in question and the managerial actions that could alter these characteristics and facilitate the occurrence of the exaptation mechanism with the entity in question. Originality/value: This process led to the development of an algorithm for analyzing the exaptation mechanism and the adaptation of the attributes associated with the agent-artifact[entity]-context tripartite to describe and analyze exaptation event, including another attribute: the type of entity.